Golgi Dynamics in Physiological and Pathological Conditions - Saraste, Jaakko; Lupashin, Vladimir; Wang, Yanzhuang; Prydz, Kristian (Frontiers Media SA, 2020)
Articles in this collection illustrate our recent progress in understanding Golgi biology, and also outline a specific set of yet unanswered Golgi-related questions. For example, exactly how do cargo and resident proteins travel to, through and out of the Golgi? What are the exact modes, carriers and molecular machineries of bi-directional Golgi trafficking? How are Golgi structure and its various functions modified during normal (differentiation, development, etc.) and abnormal (diseases, drugs, pathogens, etc.) circumstances?